Conoscenza, libertà, forma: Cassirer e i problemi fondamentali dell’estetica - Spinosa, Domenico (Aesthetica Preprint, 2021)
The present proposal intends to show on the one hand how for Cassirer addressing the issues related to the history and development of aesthetic ideas entails a necessary and decisive recognition of the transcendental thought by the German philosopher more and more in a dilated and plural way, on the other hand how this expresses fully entitled the most appropriate way to return to questioning today in general about the function and meaning of philosophy. Indeed, if one examines the long course of his studies, one realizes how much Cassirer rethinks and re-evaluates Kant’s Kritik der Urteilskraft, establishing the question of a priori in the sphere of freedom and identifying in the critical method the most proper manifestation of a ‘vital form’ oriented towards a ‘universal systematic of cultural conscience’ based on morphological themes (inherited primarily by Goethe). To highlight this, it is appropriate at first to follow the two directions that Cassirer traces: the internal analysis of the third Kritik (which the philosopher carries out above all in Kants Lehre und Leben, 1918, 1921²) and the studies on the historical development of aesthetic ideas (in particular in Freiheit und Form, 1916, 1918²). It is believed that paying attention to a philosopher like Cassirer today does not result in a purely commemorative exercise. Rather, his invitation to reconsider philosophy in a meta-reflective function still appears in our present as current and profitable in order to participate with advantage in the attempt to respond to the increasingly complex requests that come from the facts of the different sciences and knowledge.